Structure of O-Specific Side Chains of Lipopolysaccharides from Yersinia pseudotuberculosis - Samuelsson, Kurt (1974)
Lipopolysaccharide prepared from cells of Yersinia (Pasteurella) pseudotuberculosis of serogroups I, II, III, IV, and V is known to contain the 3,6-dideoxyhexose (DDH) paratose, abequose, paratose, tyvelose, and ascarylose in its respective O-specific side chains. Lipopolysaccharides or lipid-free polysaccharides of all of the 10 known serogroups and subgroups were subjected to methylation analysis and determined as alditol acetates by gas-liquid chromatography and mass spectrometry. The results indicated that the O-specific side chains of nine serotypes are composed of oligosaccharide repeating units in the form of four alternative general structures in which a terminal DDH may vary. These structures are DDH [Formula: see text] 6-deoxy-d-manno-heptose [Formula: see text] d-galactose (serogroups IA, IIA, and IVB), DDH [Formula: see text] d-mannose [Formula: see text] l-fucose (serogroups IB and IIB), and two configurations similar to the latter except that the 4-position of l-fucose was either linked to the d-mannose residue (serogroups VA and VB) or to the DDH residue (serogroups III and IVA). In contrast, O-groups in lipopolysaccharide of the newly discovered serogroup VI contained the DDH colitose and 2-acetamido-2-deoxy-d-galactose. Accordingly, all five known types of DDH have now been detected in lipopolysaccharides of Y. pseudotuberculosis. The sugar 6-deoxy-d-manno-heptose, present in O-specific side chains of serogroups IA, IIA, and IVB, has not yet been reported to occur elsewhere in nature.